Pengembangan Media Pembelajaran E-Learning Berbasis Edmodo Dengan Discovery Learning Pada Mata Pelajaran PPKN Kelas VIII Di SMP Lab Undiksha Singaraja - Sudewa, Komang Ary; Sugihartini, Nyoman; Divayana, Dewa Gede Hendra (Universitas Pendidikan Ganesha, 2021)
This study aims to produce designs and implement the development of discovery learning media based on Edmodo in the second semester of PPKn subjects at the SMP Lab Undiksha. This research is included in the type of research and development (R&D) with the ADDIE development model. This research involved VIII grade students and PPKn subject teachers at Undiksha Lab Middle School. Data were collected using a questionnaire / questionnaire. The analysis technique used is the expert validity test and the results for content experts are 1.00, design experts are 1.00, and media experts are 1.00. The results showed the results of the design and implementation of Edmodo-based discovery learning media in PPKn subjects were successfully applied based on the results of the validation test from content experts, design experts, and learning media experts with an average value of 1.00 with very valid criteria.